2020
DOI: 10.1074/jbc.ra119.012053
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary surfactant lipids inhibit infections with the pandemic H1N1 influenza virus in several animal models

Abstract: The influenza A (H1N1)pdm09 outbreak in 2009 exemplified the problems accompanying the emergence of novel influenza A virus (IAV) strains and their unanticipated virulence in populations with no pre-existing immunity. Neuraminidase inhibitors (NAIs) are currently the drugs of choice for intervention against IAV outbreaks, but there are concerns that NAI-resistant viruses can transmit to high-risk populations. These issues highlight the need for new approaches that address the annual influenza burden. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 34 publications
1
72
0
Order By: Relevance
“… 135 A wealth of in vitro and in vivo studies have demonstrated that the biophysical function of PS can be inhibited by various particles, including nanoparticles, 144 148 nanoenabled sprays and drugs, 149 , 150 PM2.5, 151 153 and pathogens such as the H1N1 influenza virus. 154 Second, particles may interfere with PS metabolism and homeostasis in the alveolar hypophase. It was found that nanoparticles caused surfactant degradation from the more surface active large aggregates to less surface active small aggregates.…”
Section: Aerosol Deposition In the Lungmentioning
confidence: 99%
“… 135 A wealth of in vitro and in vivo studies have demonstrated that the biophysical function of PS can be inhibited by various particles, including nanoparticles, 144 148 nanoenabled sprays and drugs, 149 , 150 PM2.5, 151 153 and pathogens such as the H1N1 influenza virus. 154 Second, particles may interfere with PS metabolism and homeostasis in the alveolar hypophase. It was found that nanoparticles caused surfactant degradation from the more surface active large aggregates to less surface active small aggregates.…”
Section: Aerosol Deposition In the Lungmentioning
confidence: 99%
“…It should also be noted that despite its ability to inhibit TLR activation and inflammation, PG in surfactant does not seem to be globally immunosuppressive. In fact, in animal models in vivo it protects against infection resulting from several viruses, including respiratory syncytial virus, influenza A (H3N2) and H1N1 [38] , [39] , [56] , by inhibiting the interaction of these viruses with their receptors on host cells ( Fig. 1 ).…”
Section: Additional Considerationsmentioning
confidence: 99%
“…However, intrinsic pulmonary surfactant has been found to be an important part of our innate immune system, and its use was recently shown to help prevent several respiratory viruses, such as H1N1 and influenza. [47][48][49] The pulmonary surfactant phospholipids are thought to prevent viral infections by inhibiting viral binding to epithelial cells. The use of surfactants to achieve the same results in the upper aerodigestive tract is intriguing but has not been studied.…”
Section: Agents With Antiviral Capabilitymentioning
confidence: 99%